Democratic decentralisation in India - retrospect and prospects - Palanidurai, K.V
The author has traced chronologically developments relating to establishment of Local Self-Government Institutions in the country. He has narrated the experiences of a few States which have attempted democratic decentralisation. Still, the position does not alter from 1978 which the Ashok Mehta Committee Report has excellently epitomised in the following words: "An overview of the national scene would indicate that the activities of PRIs were meagre, their resource base weak and the overall attention given to them niggardly." The author, thereafter, reviews the recent Constitution Amendment Bills (seventy second and seventy third) introduced in the Lok Sabha on the 16th September, 1991. He concludes that un
Keywords: Panchayati Raj - India; District Administration - India; Local Government; Decentralisation; Village Panchayats - India